Peer Perspectives Within the Inclusive Postsecondary Education Movement: A Systematic Review. Issue 2 (March 2021) - Carter, Erik W.; McCabe, Lauren E.
Peers play a central role in supporting college access for students with intellectual and developmental disabilities (IDD). This review examines available research addressing the perspectives of college student peers on the inclusive postsecondary education (IPSE) movement and their involvement in it. Approximately 2, 670 peers—most of whom were female and undergraduates—participated in these 37 studies. We review findings addressing the views of peers on the following topics: (a) motivations for volunteering, (b) effectiveness as a peer support, (c) challenges they encountered, (d) impact of involvement on themselves, (e) impact of IPSE on their campus, (f) recommendations for IPSE programs, and (g) attitudes regarding disability. This research collectively highlights the multiple factors that draw peers to become involved, the experiences peers have within their campus' programs, the myriad ways in which they and their campus may benefit from this movement, and their views regarding inclusion and disability. We offer recommendations for research and practice aimed soliciting the views and involvement of peers within the inclusive postsecondary education movement.